Faktor-faktor Penentu Kepuasan Pengguna I-SimPeg: Pendekatan Model UTAUT-EUCS dengan PLS-SEM - Panigoro, Nurlia; Katili, Muhammad Rifai; Lahay, Sri Nilawaty (Jambura Journal of Informatics, 2025)
Understanding user satisfaction determinants in government information systems is essential for successful digital transformation. This study examines factors influencing users' satisfaction with the Integrated Personnel Management Information System (I-SimPeg) in Bone Bolango Regency through an integrated UTAUT-EUCS model using PLS-SEM. Data collected from 358 government employees revealed that performance expectancy, effort expectancy, content, ease of use, facilitating conditions, and behavioral intention significantly influence user satisfaction. In contrast, social influence, accuracy, format, and timeliness were not significant contributors. The research demonstrates the complementary value of combining technology acceptance and end-user satisfaction models in assessing government information systems. Practical recommendations include comprehensive user training, intuitive interface development, routine maintenance protocols, automated data validation, and enhanced backup systems to improve I-SimPeg implementation in regional government agencies.Memahami faktor-faktor penentu kepuasan pengguna dalam sistem informasi pemerintahan sangat penting untuk keberhasilan transformasi digital. Penelitian ini mengkaji faktor-faktor yang mempengaruhi kepuasan pengguna Sistem Informasi Manajemen Kepegawaian Terintegrasi (I-SimPeg) di Kabupaten Bone Bolango melalui model terintegrasi UTAUT-EUCS menggunakan PLS-SEM. Data yang dikumpulkan dari 358 pegawai pemerintahan menunjukkan bahwa ekspektasi kinerja, ekspektasi usaha, isi, kemudahan penggunaan, kondisi memfasilitasi, dan minat perilaku secara signifikan mempengaruhi kepuasan pengguna, sementara pengaruh sosial, akurasi, bentuk, dan ketepatan waktu tidak berpengaruh signifikan. Penelitian ini mendemonstrasikan nilai komplementer dari penggabungan model penerimaan teknologi dan kepuasan pengguna akhir dalam mengevaluasi sistem informasi pemerintahan. Rekomendasi praktis meliputi pelatihan komprehensif bagi pengguna, pengembangan antarmuka intuitif, protokol pemeliharaan rutin, validasi data otomatis, dan peningkatan sistem backup untuk menyempurnakan implementasi I-SimPeg di instansi pemerintah daerah.